Bilingual Education of Schoolchildren as a Subject of Research of Native Scientists - Nikolska, Nina (Pedagogical Discourse, 2019)
In this article the author analyzed the content of the terms «bilingual education» and «bilingual instruction». The author claims that in pedagogical sources quite often these two concepts are used. The analysis of these two areas and their main features is carried out, the author considers it necessary to distinguish between these two concepts: bilingual education (bilingual, bicultural education) is a process, the realization of which is based on the use of two programs with the aim of mastering subjects that include cultures, from which these two languages occur. Bilingual instruction is a process in which curricula or approaches are designed to facilitate learning for non-English speakers in primary and secondary schools by teaching their native language and English. Bilingual education is a means of obtaining education using two languages as a means of teaching, in the process of which the person formation open to interaction with the outside world takes place. Since in the bilingual education non-native or foreign language process is viewed not only as a means of everyday communication, but also as the world knowledge instrument of special knowledge, as a result pupils achieve the linguistic and subject competence high integrative level. Teaching using two languages is quite common in European countries. As a rule, such training does not require artificial encouragement, since it helps to broaden the students’ general outlook by getting acquainted with the foreign culture peculiarities, creating a tolerant attitude to the views, cultural characteristics of another culture representative, related to national specifics. This process stimulates the need for further self-education and self-development, is a necessary condition for professional work in the modern world.